Central European with a Post-Socialist Limp: On the Slovene Legal Identity - Novak, Marko (Public Governance, Administration and Finances Law Review, 2023)
According to David and Grasmann, the recognised comparative law scholars, there are basically three main criteria for differentiating between legal families and their subgroups: 1. meta-legal considerations; 2. legal sources; and 3. dogmatic legal structures. Concerning the last two criteria, which could also be designated as formal elements of a country’s legal identity, Slovenia has been deeply “immersed” in the civil law of a Central European type. Even after the decline of the Habsburg Empire, what remained to apply on the territory of nowadays Slovenia as part of the then Kingdom of Yugoslavia, was to an important extent Austrian law. Moreover, even the “decadent capitalist code” such as the Allgemeines bürgerliches Gesetzbuch (ABGB) more or less survived in spite of the communist “withering away of the state and law”, and can today still be applicable to some older cases. After one thousand years of Germanic dominance, the Slovenes turned to the East in trying to build their national identity, one hundred years ago when the Empire collapsed. Although that seemed to be a necessary move towards stronger national identity, it was their first step away from the rule of law. The second step away from that was the period of communism that endured almost half a century. Nevertheless, the formal part of the Central European legal identity somehow survived in Slovene law, with certain “injuries” of course, but it is mainly the meta-legal considerations, their sociological and psychological elements in particular, that nowadays make a difference between the situations of the rule of law in the Republic of Slovenia and, for example, in the Republic of Austria, both parts of the onetime joint Empire.